Looking the organizations “backstage”: Contributions to political leadership - Miranda, Sandra (2019)
Leadership has been an active area of scientific investigation with scholars developing different perspectives on antecedents, processes and outcomes. Conspicuous in its absence has been a conceptualization of leadership from a political perspective. The objective of this investigation was to understand the political leadership in organizations specificities. In an effort to address this need, we developed an integrative theoretical model of political leadership which gathers number of variables that have been neglected so far, operationalized by 992 quests application. The variables contemplated on the analysis model are linked to antecedents of leaders political behavior (power motives, machiavellianism and political ability), leaders political behaviors (soft and hard political behaviors), to the political behavior implications of to the leaders’ political behaviors’ consequences towards the attitude of workers on organizations (organizational satisfaction, organizational commitment, organizational trust and organizational cynicism) and verifying the intromissions of variables moderator of the relationships drawn (leaders personal reputation and political climate). The implications for a political theory of leadership are discussed, as are directions for future research.